APPLICATION OF THE DMAIC METHODOLOGY IN THE MAINTENANCE SECTOR OF A SANITATION COMPANY - Guimarães Vieira, Fernanda; Gonçalves Castro Silva, Ana Cristina; de Castro Silva, José; Antônio Macedo Leite, Ângelo; Santos, Pedro Vieira Souza (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
Sanitation companies are responsible for the distribution of water and sewage treatment in cities, requiring high-quality service to ensure treated water reaches households and sewage is adequately treated. This study focuses on applying the Lean Six Sigma methodology, specifically DMAIC (Define, Measure, Analyze, Improve, Control), in the maintenance sector of a sanitation company located in the São Francisco Valley. The goal is to optimize maintenance processes, reduce failures, and improve the quality of water distribution and sewage treatment services. The implementation of the first three phases of DMAIC has already shown significant improvements in the efficiency and reliability of equipment at the Vitória Water Treatment Station (ETA) in Petrolina-PE. The approach includes identifying critical problems, accurately measuring indicators, and analyzing root causes, resulting in robust interventions. It was observed that organizational causes have a greater predominance in triggering problems in the maintenance sector, contributing to human and physical causes as well, requiring special attention. To sustain these improvements in the long term, continuous monitoring of indicators and investment in team training are recommended, promoting a culture of continuous improvement and positively impacting the quality of services provided to the population.